Lysolipids in Vascular Development, Biology, and Disease. Issue 2 (February 2021) - Engelbrecht, Eric; MacRae, Calum A.; Hla, Timothy
Abstract : Membrane phospholipid metabolism forms lysophospholipids, which possess unique biochemical and biophysical properties that influence membrane structure and dynamics. However, lysophospholipids also function as ligands for G-protein–coupled receptors that influence embryonic development, postnatal physiology, and disease. The 2 most well-studied species—lysophosphatidic acid and S1P (sphingosine 1-phosphate)—are particularly relevant to vascular development, physiology, and cardiovascular diseases. This review summarizes the role of lysophosphatidic acid and S1P in vascular developmental processes, endothelial cell biology, and their roles in cardiovascular disease processes. In addition, we also point out the apparent connections between lysophospholipid biology and the Wnt (int/wingless family) pathway, an evolutionarily conserved fundamental developmental signaling system. The discovery that components of the lysophospholipid signaling system are key genetic determinants of cardiovascular disease has warranted current and future research in this field. As pharmacological approaches to modulate lysophospholipid signaling have entered the clinical sphere, new findings in this field promise to influence novel therapeutic strategies in cardiovascular diseases.